Introduction to Characteristics of Authenticity in Rupiah Based on Augmented Reality - Euis Nur Fitriani Dewi; Andi Nur Rachman; Arif Muhamad Nurdin (IJAIT (International Journal of Applied Information Technology), 2022)
This research is developing an application introduction to the characteristics of the authenticity of the rupiah by applying a system of Augmented Reality (AR) on android mobile devices. The Act of forgery of currency has a broad impact and is very detrimental to society. Congressional education applications introduction to the characteristics of the authenticity of the rupiah using augmented reality technology by applying techniques of marker-based tracking. This research made RUPIAR with the Multimedia Development Life Cycle (MDLC) method. Based on the testing that has been done, the results of the alpha testing are already functionally fit. From beta testing, test results from User Acceptance of functionality Test (UAT) obtained the value of 89.68%, declared eligible for use with the interpretation "Good", which means the application is worthy of being used and can be developed.